Thoracic Spine Localization Using Preoperative Placement of Fiducial Markers and Subsequent CT. A Technical Report - Anaizi, Amjad Nasr; Kalhorn, Christopher; McCullough, Michael; Voyadzis, Jean-Marc; Sandhu, Faheem A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Study Design A retrospective case series evaluating the use of fiducial markers with subsequent computed tomography (CT) or CT myelography for intraoperative localization.Objective To evaluate the safety and utility of preoperative fiducial placement, confirmed with CT myelography, for intraoperative localization of thoracic spinal levels.Summary of Background Data Thoracic spine surgery is associated with serious complications, not the least of which is the potential for wrong-level surgery. Intraoperative fluoroscopy is often used but can be unreliable due to the patient's body habitus and anatomical variation.Methods Sixteen patients with thoracic spine pathology requiring surgical intervention underwent preoperative fiducial placement at the pedicle of the level of interest in the interventional radiology suite. CT or CT myelogram was then done to evaluate fiducial location relative to the level of pathology. Surgical treatment followed at a later date in all patients.Results All patients underwent preoperative fiducial placement and CT or CT myelography, which was done on an outpatient basis in 14 of the 16 patients. Intraoperatively, fiducial localization was easily and quickly done with intraoperative fluoroscopy leading to correct localization of spinal level in all cases. All patients had symptomatic improvement following surgery. There were no complications from preoperative localization or operative intervention.Conclusions Preoperative placement of fiducial markers confirmed with a CT or CT myelogram allows for reliable and fast intraoperative localization of the spinal level of interest with minimal risks and potential complications to the patient. In most cases, a noncontrast CT should be sufficient. This should be an equally reliable means of localization while further decreasing potential for complications. CT myelography should be reserved for pathology that is not evident on noncontrast CT. Accuracy of localization is independent of variations in rib number or vertebral segmentation. The technique is a safe, reliable, and rapid means of localizing spinal level during surgery.
Keywords: spine localization; thoracic discectomy; thoracic spine; wrong level; surgery; thoracic disc